Numerical Studies and Analyses on the Acidizing Process in Vug Carbonate Rocks - Jia, Cunqi; Sepehrnoori, Kamy; Zhang, Haiyang; Yao, Jun (Frontiers in Earth Science, 2021)
A vug porosity system, in addition to matrix, is also the target rocks for the acidizing. In this work, the acidizing process in two typical core-scale separate-vug porosity systems are studied in detail. Numerous cases are conducted to discuss a parametric study on the acidizing process and hydraulic behavior. Results indicate that the presence of vug reduces the pore volume of acid solution consumed to achieve a breakthrough, which is consistent with experimental observations. Increasing vug diameter and porosity decrease pore volume to breakthrough both for vugular carbonate rock and isolated vug carbonate rock. In comparison, acid mass does not change a lot. Typical dissolution patterns can also be observed in the acidizing process when vug exists. Compared to matrix dissolution patterns, the presence of vug induces wormhole to pass through the vug region.